2022
DOI: 10.1186/s12978-022-01479-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive coercion and abuse among pregnancy counselling clients in Australia: trends and directions

Abstract: Background Reproductive coercion and abuse (RCA) interferes with a person’s reproductive autonomy and can be classified into behaviours that are pregnancy promoting or pregnancy preventing (including coerced abortion). However, prevalence data are lacking, and little is known about whether particular forms of RCA are more or less common. The aims of our study were to explore how frequently people seeking pregnancy counselling reported RCA, the proportions reporting the different forms of RCA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Initial research on reproductive coercion shows that approximately 0.1–0.5% of women have experienced abortion coercion, in which their partner attempts to control the outcome of a pregnancy by pressuring them into terminating it (Chibber et al, 2014; Finer et al, 2005). More recent research has identified that victimization rates of pregnancy-preventing forms of reproductive coercion are equivalent to pregnancy-promoting forms of reproductive coercion (Sheeran et al, 2022). This study reported that approximately 7.5% of their sample had experienced abortion coercion or physical violence that was meant to induce miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Initial research on reproductive coercion shows that approximately 0.1–0.5% of women have experienced abortion coercion, in which their partner attempts to control the outcome of a pregnancy by pressuring them into terminating it (Chibber et al, 2014; Finer et al, 2005). More recent research has identified that victimization rates of pregnancy-preventing forms of reproductive coercion are equivalent to pregnancy-promoting forms of reproductive coercion (Sheeran et al, 2022). This study reported that approximately 7.5% of their sample had experienced abortion coercion or physical violence that was meant to induce miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Research exploring the prevalence of violence against women in Australia demonstrates that one in five women over the age of 15 will experience violence in their lifetime [ 8 ]. Further, a recent study found 15% of women attending two family planning clinics had experienced reproductive control and abuse, which included pregnancy prevention and abortion [ 9 ]. Public health practice widely accepts that gender inequality is the underlying cause of all forms of violence against women [ 10 – 14 ].…”
Section: Introductionmentioning
confidence: 99%